A re-evaluation of 9-HODE activity at TRPV1 channels in comparison with anandamide: enantioselectivity and effects at other TRP channels and in sensory neurons - De Petrocellis, Luciano (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: Two oxidation products of linoleic acid, 9- and 13-hydroxy-octadecadienoic acids (HODEs), have recently been suggested to act as endovanilloids, that is, endogenous agonists of transient receptor potential vanilloid-1 (TRPV1) channels, thereby contributing to inflammatory hyperalgesia in rats. However, HODE activity at rat TRPV1 in comparison with the best established endovanilloid, anandamide, and its enantioselectivity and selectivity towards other TRP channels that are also abundant in sensory neurons have never been investigated. EXPERIMENTAL APPROACH: We studied the effect of 9(R)-HODE, 9(S)-HODE, (+/–)13-HODE, 15(S)-hydroxyanandamide and anandamide on [Ca(2+)](i) in HEK-293 cells stably expressing the rat or human recombinant TRPV1, or rat recombinant TRPV2, TRPA1 or TRPM8, and also the effect of 9(S)-HODE in rat dorsal root ganglion (DRG) neurons by calcium imaging. KEY RESULTS: Anandamide and 15(S)-hydroxyanandamide were the most potent endovanilloids at human TRPV1, whereas 9(S)-HODE was approximately threefold less efficacious and 75- and 3-fold less potent, respectively, and did not perform much better at rat TRPV1. The 9(R)-HODE and (+/–)13-HODE were almost inactive at TRPV1. Unlike anandamide and 15(S)-hydroxyanandamide, all HODEs were very weak at desensitizing TRPV1 to the action of capsaicin, but activated rat TRPV2 [only (+/–)13-HODE] and rat TRPA1, and antagonized rat TRPM8, at concentrations higher than those required to activate TRPV1. Finally, 9(S)-HODE elevated [Ca(2+)](i) in DRG neurons almost exclusively in capsaicin-sensitive cells but only at concentrations between 25 and 100 μM. CONCLUSIONS AND IMPLICATIONS: The present data suggest that HODEs are less important endovanilloids than anandamide. LINKED ARTICLES: This article is part of a themed section on Cannabinoids. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2012.167.issue-8